Children education for sustainable control of liver fluke infections - Men-Bao Qian; Xiao-Nong Zhou (BMC, 2022)
Abstract Significant disease burden is caused by infections with human liver flukes, including Clonorchis sinensis, Opisthorchis viverrini and O. felineus. Epidemiology is characterized by high burden in the male than the female, and in the elder than the younger. Chemotherapy is the mainstream for morbidity control, but it could not prevent re-infection. Meanwhile, behavioral change on the dietary habit of ingesting raw freshwater fish is challenging. In this opinion, we argue why it is important to educate children for sustainable control of liver fluke infections. Then, the design, development and key messages of an educational cartoon for preventing liver fluke infections is introduced. Technical focuses are emphasized based on a pilot using the education cartoon for preventing clonorchiasis in China. Finally, how to further develop and verify this education strategy is discussed. Graphical Abstract